Social values and health policy: a new international research programme - Littlejohns, Peter; Weale, Albert; Chalkidou, Kalipso; Faden, Ruth; Teerawattananon, Yot (Journal of health organization and management, 2012)
Purpose - This editorial aims to outline the context of healthcare priority-setting, and summarise each of the other ten papers in this special edition. It introduces a new multidisciplinary research programme drawing on ethics, philosophy, health economics, political science and health technology assessment, out of which the papers in this edition have arisen.Design methodology approach - Key normative concepts are introduced and policy and research context provided to frame subsequent papers in the edition.Findings - Common challenges of health priority-setting are faced by many countries across the world, and a range of social value judgments is in play as resource allocation decisions are made. Although the challenges faced by different countries are in many ways similar, the way in which social values affect the processes and content of priority-setting decisions means that those challenges are resolved very differently in a variety of social, political, cultural and institutional settings, as subsequent papers in this edition demonstrate. How social values affect decision making in this way is the subject of a new multi-disciplinary research programme.Originality value - Technical analyses of health priority setting are commonplace, but approaching the issues from the perspective of social values and conducting comparative analyses across countries with very different cultural, social and institutional contexts provides the content for a new research agenda.